TASK-BASED LEARNING EVALUATION INSTRUMENTS BY THE DEVELOPMENT OF CHILDREN WITH NUANCES ISLAMIC EDUCATION AT TPA (CHILDREN PARK) FOUNDATION PPAW KOLAKA - Umajjah, Nur Thahirah (Jurnal Teknologi Pendidikan Madrasah, 2022)
This research is oriented towards learning evaluation instruments at TPA Al Mawaddah Warrahmah Kolaka. TPA Al Mawaddah Warrahmah Kolaka provides care and learning facilities for children aged 0-3 years. The concept of the resulting learning instrument is an evaluation instrument based on child development with the nuances of Islamic education. This instrument contains indicators of student development in terms of cognitive, language, motor and socioemotional abilities with age division: (1) 0-12 months, (2) 1-2 years, (3) 2-3 years, (4) 3 -4 years.